Manfaat dan Hambatan Problem-Based Learning (PBL) Menurut Perspektif Mahasiswa Baru di Fakultas Kedokteran Universitas Riau - Enkarmila Asni; M Yulis Hamidy (Jurnal Ilmu Kedokteran, 2010)
Problem-based learning (PBL) has been adopted in medical faculty and sometimes produced students’ anxieties. Thisqualitative research will gathered the information of students’ condition based on their perspectives in strengths anddifficulties of adapting PBL in Medical Faculty of Riau University. Data were collected by questionnaires and reflectiveassay. These data will be analyzed and grouped based on the themes and meaning by researcher. Result showed that thestrengths of PBL based on students perspectives were increasing in skill of teamwork, speaking, active learning,communicating, and critical thinking. In the other hand, students’ perspectives of PB L difficulties after first tutorialwere internal types such as lack of knowledge in PBL and in topic of discussion, but after first session, the difficultieswere external types such as; heavy workload, limited sources of literatures.